The Kinds of Translation Error Made by the Students in Writing Abstract of the Theses and Dissertations - Munawir Munawir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Buton, 2020)
This research aims to find the kinds of translation error made in writing abstract of theses and dissertations. This research used descriptive quantitative method to analyze and expose the errors of abstracts of theses and dissertations. The data of this research was the abstracts of theses and dissertations of universities in Makassar. It took 61 abstracts of theses and dissertations from different universities. The abstracts is analyzed by using error analysis technique. The result of this research concluded that the abstracts are found various errors. Errors in the kinds of translation were Omission – Deviation – Modification – Addition - and the least is Inversion. The result of this research provides a new information about translation to the students especially to non-English students, and motivate them to translate the abstract well.